Dimensão educativa do trabalho: estudo de caso da associação de bordadeiras do Seridó ABS- Caicó/ Rio Grande do Norte - Froes, César Quintão (2011)
This current work s contains issues about the educative dimension of work and its organization s process and managing for it own professionals. It aims to understand how the skills and pedagogic process, in a educative praxis perspective. Are based in a new culture of work of education process an work managing by workers in Handcraft Association of Serido/ Caicó/ RN. It uses as a methodologic-theoric reference cases s study approach, selecting the procedures of part extructure interview. It was done with six embroidereses from the Handcraft Association. The research shows that the educative process of learning and knowledges construction, in the work and by the work. Those processes develop in exchange experiences net in a friendly economic environment and raise elements of a work culture personal that work there. The embroidereses learn how to embroid doing the job and this learning, a lot of times, is influenced by the life conditions, residence local and infantile work in the country area and the living to the urban area, particularly to Caicó. The knowledge relation between them is the matter fact in the embroider learning process that means a social relation based on the knowledge differences between their position in its structure involving the work division, that each handcraft maker knows every part of the embroider, type of work or machine type, step by step until the work is done. It involves decision, execution and machine movements repetition, the focus are the categories that fit in current flexible financial issue. They schedule the work at home so they have time to do other stuff. Most part of the production currently is done to obey de a certain request that aims as production target, being a homework. Another important issue is the embroider work time: time and experience that is within in the professional life and its knowledge representation of job/profession. This time is got as a acquisition process of certain a work dominion and self knowing; time added to changes that were being there practicing from the new characteristics in the furniture, clothes and towels that are in the introduction communicative and its effect. In this way this work include articulations process among skills, educative process and handcraft work organization that allowed the interpretation and finish, that are related to the case study and its developments: handcraft embroidered considered as a profession, money source not conventional where is not work available and a temporary activity while studyng, homework and flexible work